Self-Efficacy in Entrepreneurship for Science Teacher Candidates: A Comparative Study of Gender and Semester - M. Harja Efendi; M. Khairul Wazni; Agus Muliadi (Postgraduate, University of Mataram, 2023)
This study aims to determine differences in student perceptions about self-efficacy in the field of entrepreneurship based on gender and semester. This study is an exploratory research with 35 biology education students as subjects. The research instrument used was a closed questionnaire with degraded answers according to a Likert scale that had been declared valid. Analysis of research data used is descriptive statistics and inferential statistics with t-test and Anova test at a significance level of 5%. The results of the study show that (1) students' perceptions of self-efficacy in the field of entrepreneurship has an average score of male students at 3.16 with the Good category and women at 3.10, while semester IV students are at 3.09 with the Good category, semester VI is at 3.12 with the Good category, and semester VIII of 3.15 in the Good category; (2) there is no significant difference in students' perceptions of self-efficacy in the field of entrepreneurship between male and female gender, as evidenced by a significance value of 0.716 greater than the alpha testing value of 0.05 (>0.05); (3) there is no significant difference in the perceptions of semester IV, VI, VIII students about self-efficacy in the field of entrepreneurship as evidenced by a significance value of 0.959 greater than the alpha testing value of 0.05 (>0.05).